2017
DOI: 10.4028/www.scientific.net/kem.730.141
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ion Release and Cytotoxicity of Titanium Orthodontic Miniscrews

Abstract: The aim of this study was to investigate the metal ion release and cytotoxicity of MU orthodontic miniscrews as well as two other brands of orthodontic miniscrews over time. Twenty-four orthodontic miniscrews were tested, divided into three groups of eight. Each sample extraction was performed following the ISO 10993-12:2012 method. Solutions were collected after 1, 7, and 30 days (T1, T2, and T3). The supernatants extracted from these three groups were added and exposed to mouse L929 fibroblastic cell line us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The increase in dental plaque and calculus accumulation could have various drawbacks as the increased acidity of saliva, abnormal inflammatory response, and /or biocorrosion and failure of MSIs. [5][6][7] These results were in agreement with previous studies that reported significantly increased accumulation of dental plaque, increased incidence of white spot lesion and caries occurrence during the first six months of fixed orthodontic appliance insertion. 26,27 The Comet assay was a widely used biomonitoring tool for DNA damage and the buccal cell model constitutes an attractive and potentially useful tool for investigating in vivo effects on DNA damage of dietary agents, lifestyle choices, chemical agents and xenobiotics in general.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The increase in dental plaque and calculus accumulation could have various drawbacks as the increased acidity of saliva, abnormal inflammatory response, and /or biocorrosion and failure of MSIs. [5][6][7] These results were in agreement with previous studies that reported significantly increased accumulation of dental plaque, increased incidence of white spot lesion and caries occurrence during the first six months of fixed orthodontic appliance insertion. 26,27 The Comet assay was a widely used biomonitoring tool for DNA damage and the buccal cell model constitutes an attractive and potentially useful tool for investigating in vivo effects on DNA damage of dietary agents, lifestyle choices, chemical agents and xenobiotics in general.…”
Section: Discussionsupporting
confidence: 92%
“…[2][3][4] Into the oral envelope, various factors as saliva, oral fluids, the enzymatic behavior, microbial activity, pH fluctuation, and temperature fluctuation interact together, creating an ideal condition for aqueous corrosion of implanted metals and alloys giving rise to potential metal ion release. [5][6][7] The released metal ions (titanium, aluminum, and vanadium) could induce localized inflammation, clinical failure of the MSIs, cutaneous allergic reactions, hypersensitivity, cytotoxicity, carcinogenesis, and possible genotoxicity. [8][9][10][11] The clinical studies 7,12 evaluating the cytotoxic effects of metal ions released from orthodontic miniscrew implants in body fluids were limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples of the tested material and controls (ISO 10993-12:2012 recommends appropriate positive and negative reference materials) are placed on the solidified agar (note that any absorbent material needs to be pre-soaked with the medium before being placed on the agar) and allowed to diffuse through the monolayer of cells. Cell lysis under and surrounding the specimens, as well as changes in general shape, vacuolization, detachment, and membrane integrity, are observed microscopically after 24-72 hours of incubation [80,86].…”
Section: Biomaterials Cytotoxicity Assaymentioning
confidence: 99%
“…The study of physical, chemical and morphological properties, structure of implants is one of the priority tasks of condensed matter physics and medical materials science. Metals and alloys currently used for the implant production are titanium, titanium alloys, certain steel grades, cobalt-chromium alloys, etc., which have high strength and anticorrosion properties and do not contain such toxic alloying elements as Al and V [1][2][3][4]. The development of biocompatible low-modulus β-alloys, in particular, Ti-Zr and Ti-Nb systems, has become a new direction in medical materials science.…”
Section: Introductionmentioning
confidence: 99%